Smart Technologies and Innovations in Design for Control of Technological Processes and Objects: Economy and Production Proceeding of the International Science and Technology Conference "FarEastСon-2018" Volume 2 - Solovev, Denis B. (Smart Innovation, Systems and Technologies, 2019)
This book features selected papers presented at The International Science and Technology Conference "FarEastCon", which took place on October 2-4, 2018 in Vladivostok, Russian Federation. The conference represents an informational platform for accumulating expert opinion on projects and initiatives aimed at the implementation of farsighted scientific research and development; it also allows scientific and practical achievements to be shared with a wide circle of researchers. Sections of the conference are of interest for the broad range of experts involved in developing innovative solutions and organizing events that increase the efficiency of economic and innovative activities.